2014
DOI: 10.5762/kais.2014.15.3.1691
|View full text |Cite
|
Sign up to set email alerts
|

Software Implementation of WAVE Security Algorithms

Abstract: IEEE developing WAVE specifications are able to support V2V and V2I wireless communications, and these functionalities can be used to enhance vehicle operational safety. To overcome any security weaknesses that are inherent in wireless communications, WAVE specification should support message encryption and authentication functions. In this study, we have implemented WAVE security algorithms in IEEE P1609.2 with openssl library and C language. We have verified the normal operation of implemented software, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The proposed method uses different formats for key generation and messaging. The message formats are adopted from [24] and [39].…”
Section: Communication Cost Of the Proposed Methodsmentioning
confidence: 99%
“…The proposed method uses different formats for key generation and messaging. The message formats are adopted from [24] and [39].…”
Section: Communication Cost Of the Proposed Methodsmentioning
confidence: 99%
“…Their experimental analysis indicates that the IEEE 1609.2 standard based on ECDSA is highly demanding in the resource. In [ 27 ], the authors reported software implementation of the IEEE 1609.2 standard using the OpenSSL security library.…”
Section: Related Workmentioning
confidence: 99%